Ethics in information technology - Reynolds, George W. (Australia : Cengage Learning Asia Pte Ltd, 2009)
Ethics in Information Technology, Second Edition is a highly anticipated revision offering updated and newsworthy coverage of issues such as file sharing, infringement of intellectual property, security risks, Internet crime, identity theft, employee surveillance, privacy, and compliance. This book offers an excellent foundation in ethical decision-making for current and future business managers and IT professionals.
An overview of ethics -- Ethics for IT professionals and IT users -- Computer and internet crime -- Privacy -- Freedom of expression -- Intellectual property -- Software development -- Employer/employee issues -- The impact of information technology on the quality of life.
Includes bibliographical references and index.
Keywords: INFORMATION TECHNOLOGY -- MORAL AND ETHICAL ASPECTS